Creative Innovation: Modernizing the Traditional Game Teng-Teng - Suhaimi, Nurnisaa; Amal , Moh Alfi; Azis, Chusnul Chatimah (International Journal of Health, Medicine, and Sports, 2024)
Amid the rapid advancement of technology, today’s younger generation increasingly spends their time on smartphones and video games as sources of entertainment and recreation. Unfortunately, many modern games lack the physical interaction and direct communication that are the hallmarks of traditional games. One traditional game that remains known to this day is Ketingting. This game is not only enjoyable but also beneficial for the mental and physical development of its players. Therefore, an innovative adaptation called Ketingting Think has been developed to make this game more unique and creative. With its appealing design and vibrant colors, Ketingting Think is expected to attract the interest of today’s youth. Based on preliminary research conducted in Malaysia, 25% of respondents agreed that this innovation is appealing. Additionally, 35% of respondents felt that this game requires strategy and creativity due to its unique gameplay. Furthermore, 40% of respondents stated that when played in groups, this game can foster teamwork and communication skills, as each team member must communicate and collaborate to win. This innovation aims not only to modernize a traditional game in Malaysia but also to introduce it to Indonesia, so that this cultural heritage can be appreciated by a wider audience.